Association between excess weight and self-reported depressive symptoms among women of childbearing age in Peru - García Ubillús, Jossy Elena (2024)
Objective: To evaluate the relationship between excess weight and the occurrence of depressive symptoms among women of childbearing age (15 to 49 years old) and to identify associated risk factors. Materials and methods: This is a cross-sectional analytical study based on secondary databases from the 2022 Encuesta Demgráfica y de Salud Familiar (ENDES - Demographic and Family Health Survey). The occurrence or absence of depressive symptoms was evaluated using the Patient Health Questionnaire (PHQ-9). Frequencies, percentages and 95 % confidence intervals were estimated. Additionally, a bivariate analysis was conducted using Pearson's chi-square test, and crude and adjusted odds ratios were calculated using a binary logistic regression model. Results: The study population included 13,492 records, with a prevalence of depressive symptoms of 8.7 %. Moreover, we found overweight and obesity in 38.7 % and 29 % of this population, respectively. The results revealed no significant association between excess weight and depressive symptoms. The adjusted odds ratios did not demonstrate a consistent relationship: overweight vs. normal weight (OR = 0.98, 95 % CI = 0.77–1.26) and obesity vs. normal weight (OR = 1.11, 95 % CI = 0.86–1.44). Despite not finding a significant association between these two main variables, other factors—such as lack of education, living in urban areas, not having a significant other, having diabetes mellitus (DM) and being a victim of emotional and physical violence—notably increased the likelihood of experiencing depressive symptoms. Conclusions: No direct association was found between excess weight and the occurrence of depressive symptoms among women of childbearing age. However, the study evidenced the importance of variables such as lack of education, not having a partner (married or not), living in urban areas, having a history of DM and hypertension (HTN), and being a victim of physical and emotional violence, which behaved as significant risk factors. This highlights the necessity of considering multiple aspects beyond body weight when addressing mental health in this population.